1999
DOI: 10.1046/j.1365-2222.1999.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of carbohydrate moieties in IgE binding to allergenic components of Cupressus arizonica pollen extract

Abstract: A large portion of the IgE reactivity of Cupressaceae-allergic subjects appears to be associated with sugar moieties of C. arizonica extract which appear to be shared by bromelain and phospholipase A2, thus suggesting that the IgE of patients reacting with such epitopes probably react with beta 1 --> 2 xylose, alpha 1 --> 3 fucose and/or alpha 1 --> 6 fucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 42 publications
(53 reference statements)
4
36
0
Order By: Relevance
“…From the comparison of their Asn-linked carbohydrate structures, the β(1,2)xylose residue and the α(1,3)fucose residue are proposed to be cross-reactive determinants. These carbohydrate residues have already been reported as cross-reactive epitopes on antigens in pollen and vegetable foods [27, 28, 29, 30]. Thus, it can be concluded that the CCDs of the latex β-1,3-glucanase isoenzymes are primarily responsible for the IgE-binding capacity and cross-reactivity observed in in vitro IgE tests.…”
Section: Discussionmentioning
confidence: 70%
“…From the comparison of their Asn-linked carbohydrate structures, the β(1,2)xylose residue and the α(1,3)fucose residue are proposed to be cross-reactive determinants. These carbohydrate residues have already been reported as cross-reactive epitopes on antigens in pollen and vegetable foods [27, 28, 29, 30]. Thus, it can be concluded that the CCDs of the latex β-1,3-glucanase isoenzymes are primarily responsible for the IgE-binding capacity and cross-reactivity observed in in vitro IgE tests.…”
Section: Discussionmentioning
confidence: 70%
“…Polygalacturonase, pollen-specific protein C13 (Os09g39950), ␤-expansin Os-EXPB13, and ␤-expansin have been well documented as pollen allergens (43)(44)(45). Previous investigations showed that most pollen allergens were glycoproteins, whereas glycan probably contributes to their allergenic activity (46). And Os09g39950 contains the function domain pfam01190 of the Ole e I family, and its homolog Ole e10 from olive pollen tubes has been detected to bind 1,3-␤-glucans preferentially (45).…”
Section: Identification Of Proteins Involved In Pollen Germinationmentioning
confidence: 99%
“…These structures could also explain the presence of specific IgE antibodies to allergens in the sera of patients without evidence of previous exposure to the allergenic source. The presence of CCDs recognised by human IgE has been reported for the purified major allergen of C. japonica, Cry j 1 [43, 44], and for C. arizonica pollen extract [76]and the purified major allergen Cup a 1 [53]. In these cases, deglycosylation treatment of the glycoallergens results in a reduced IgE-binding capability.…”
Section: Allergenic Cross-reactivitymentioning
confidence: 99%